Influence of crowded cellular environments on protein folding, binding, and oligomerization: Biological consequences and potentials of atomistic modeling. Issue 8 (5th February 2013) - Zhou, Huan-Xiang
Abstract : Recent experiments inside cells and in cytomimetic conditions have demonstrated that the crowded environments found therein can significantly reshape the energy landscapes of individual protein molecules and their oligomers. The resulting shifts in populations of conformational and oligomeric states have numerous biological consequences, e.g., concerning the efficiency of replication and transcription, the development of aggregation‐related diseases, and the efficacy of small‐molecule drugs. Some of the effects of crowding can be anticipated from hard‐particle theoretical models, but the in vitro and in vivo measurements indicate that these effects are often subtle and complex. These observations, coupled with recent computational studies at the atomistic level, suggest that the latter detailed modeling may be required to yield a quantitative understanding on the influence of crowded cellular environments.